PENYULUHAN PENGGUNAAN PUPUK KOMPOS SAMPAH ORGANIK UNTUK TANAMAN UBI KAYU PADA KELOMPOK TANI - Mulyati, Sri; Nasution, Hasriati; Yusfaneti, Yusfaneti; Maryani, Anis Tatik (DEVOSI, 2024)
The sumber rezeki farmer group grows a lot of cassava plants because they can be used as food and a source of income, but the yield of cassava plants is still very low, while national production has reached high figures. The service method applies counseling and demonstration. Counseling is carried out in the form of material counseling and direct demonstration in the field for 7 months starting from a preliminary survey, determining the schedule and implementing counseling in making compost fertilizer from organic waste materials and its use for cassava plants planted on the ground in the field. The extension was carried out in two stages, namely providing material information on how and the benefits of making compost fertilizer on cassava plants in the Sumber Rezeki Farmer Group in Mendalo Darat Village, Muaro Jambi Regency. Based on the results of the counseling, the Sumber Rezeki Farmer Group was very enthusiastic in participating in the counseling held by the service team from the Faculty of Agriculture, Jambi University. Where farmers who are members of the Sumber Rezeki farmer group feel satisfied and enthusiastic and can add skills in making organic waste compost so that they can reduce the cost of buying fertilizer for cassava plants.